Analysis of carbohydrates in Saponaria officinalis L. using GC/MS method - Liudmyla Slobodianiuk; Liliia Budniak; Svitlana Marchyshyn; Liliya Kostyshyn; Oleksandr Zakharchuk (Pensoft Publishers, 2021)
Saponaria officinalis L. (common soapwort), usually named fuller's herb, is encountered in most of Europe, in Spain, France, Italy, for example, and also in Syria and North Africa. Saponaria officinalis L. is known in most of the world as an introduced species, often a weed, and sometimes as cultivated decorative plant. Saponaria officinalis contains a large amount of saponins, which foam during extraction with water. In addition to saponins, common soapwort also contains flavonoids, quillaic acid, fatty acids and different phenolic compounds. There is a lack of information about carbohydrates content of common soapwort. Thus the aim of this study was to determine the content of carbohydrates Saponaria officinalis L. herb and roots. The qualitative composition and quantitative content of carbohydrates in herb and roots of Saponaria officinalis L. were determined by using GC/MS method. The studies have shown that Saponaria officinalis L. herb is mainly composed of free carbohydrates such as D-glucose (3.65 mg/g), D-galactose (0.29 mg/g), D-fructose (0.20 mg/g) and D-saccharose (3.72 mg/g). In common soapwort herb, after acidic hydrolysis and derivatization with acetylated aldononitriles, D-arabinose, D-fucose, D-mannose, D-glucose, D-galactose, D-fructose and Myo-inositol were identified. Free carbohydrates in the roots of Saponaria officinalis L., including D-glucose, D-galactose and D-saccharose, were determined with GC/MS method too. D-saccharose was common among free carbohydrates of Saponaria officinalis L. in the largest amounts. Its content in herb and roots of the common soapwort was 3.72 mg/g and 25.39 mg/g respectively.